PENGARUH PELATIHAN TERHADAP KINERJA KARYAWAN PADA PTPELABUHAN INDONESIA IV (PERSERO) MAKASSAR - Naidah, HJ; MS, Yanti (Perpustakaan dan Penerbitan Unismuh Makassar, 2017)
The purpose of this study is to analyze whether there is a positive effect of training implementation. The type of this research is quantitative research whose data consists of primary data and secondary data. Retrieval of data directly from the stock of questionnaires distributed to employees at the office of PT Pelabuhan Indonesia IV (Persero) Makassar. To include these primary data the authors use research instruments in the form of questionnaires and for secondary data from interviews, literature studies such as books, articles, references from various sources, and other related sources. In this research, the sample samples are 50 (fifty) respondents from 100 population who are employees in PT Pelabuhan Indonesia IV (Persero) Makassar office by determining the number of samples with slovin formula. Simple process analysis is simple linear regression. Based on the results of data analysis, the regression obtained is Y = 0.312 + 1.086 X. The result of t test shows that thitung = 8,218 with significance value 0,000 <0,05 then Ho and H1, which means there is significant influence on Training variable (X) for employee performance variable (Y).